A Legionella's outbreak in a COVID-19 pandemic setting. Issue 5 (27th May 2022) - Oliveira, Catarina; Leite, Carla; Rodrigues, Helena; Fonseca, Fernando
Abstract : In this report, the author intends to reinforce the need to test for another potencial causes of pneumonia which present with similar symptoms of SARS-CoV-2 infection and can also be responsible for outbreaks and sometimes fatal, particularly Legionnaires' disease. Legionellabacteria are aerobic, gram-negative, ubiquitous freshwater and soil inhabitants. Pneumonia is the most commonly described manifestation of Legionella infection (Legionnaires' disease), acquired through inhalation of aerosolized water droplets containing the bacteria. Legionella pneumophilais the most consistently reported species, being an important cause of severe community-acquired pneumonia that often requires hospitalization and is fatal in approximately 10% of cases. Most cases present sporadically, however, outbreaks can occur when there are appropriate conditions for bacteria to grow and spread, like stagnating water in piping systems in large facilities. Furthermore, the pathogenesis of Legionella pneumonia is complex and it is clinically and radiographically similar to other forms of pneumonia. In the context of pandemic COVID-19, the use of Legionella urinary antigen testing continues to be crucial and strongly recommended. Thus, in the outbreak faced in the author's hospital, this screening method proved to be effective and all cases of Legionellapneumonia were promptly recognized and notified, allowing public health measures to be taken to prevent the development of other potencial clusters.